Rosiglitazone pretreatment protects against lipopolysaccharide-induced fetal demise through inhibiting placental inflammation. (5th March 2016) - Bo, Qing-Li; Chen, Yuan-Hua; Yu, Zhen; Fu, Lin; Zhou, Yan; Zhang, Gui-Bin; Wang, Hua; Zhang, Zhi-Hui; Xu, De-Xiang
Abstract: Peroxisome proliferator-activated receptor (PPAR)-γ is highly expressed in human and rodent placentas. Nevertheless, its function remains obscure. The present study investigated the effects of rosiglitazone, a PPAR-γ agonist, on LPS-induced fetal death. All pregnant mice except controls were intraperitoneally injected with LPS (150 μg/kg) daily from gestational day (GD)15 to GD17. As expected, maternal LPS injection caused placental inflammation and resulted in 63.6% fetal death in dams that completed the pregnancy. Interestingly, LPS-induced fetal mortality was reduced to 16.0% when pregnant mice were pretreated with RSG. Additional experiment showed that rosiglitazone pretreatment inhibited LPS-induced expressions of tumor necrosis factor ( Tnf )- α, interleukin ( Il )- 1β, Il-6, macrophage inflammatory protein ( Mip )- 2 and keratinocyte-derived chemokine ( Kc ) in mouse placenta. Although rosiglitazone had little effect on LPS-evoked elevation of IL-10 in amniotic fluid, it alleviated LPS-evoked release of TNF-α and MIP-2 in amniotic fluid. Further analysis showed that pretreatment with rosiglitazone, which activated placental PPAR-γ signaling, simultaneously suppressed LPS-evoked nuclear factor kappa B (NF-κB) activation and blocked nuclear translocation of NF-κB p65 and p50 subunits in trophoblast giant cells of the labyrinth layer. These results provide a mechanistic explanation for PPAR-γ-mediated anti-inflammatory activity in the placentas. Overall, the present study provides additional evidence for roles of PPAR-γ as an important regulator of placental inflammation. Highlights: RSG pretreatment alleviates LPS-induced fetal death in mice. RSG activates PPAR-γ signaling in mouse placenta. RSG pretreatment inhibits LPS-evoked placental NF-κB activation. RSG blocks LPS-induced nuclear translocation of placental NF-κB p65 and p50 subunits. RSG inhibits LPS-induced placental inflammation through activating PPAR-γ signaling.